(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2018)
The research aims to shed light on one of the phenomena that have spread in the cities of Iraq, represented by the cities and the revival of the slum, which was built in irregular beating regulations and laws pertaining to zoning and land use within the Iraqi city of urban space, which led to distortion and change the features of morphological Iraqi city and in particular the city of Mahmudiya model for this emergency demographic phenomenon, as it has been the study of three residential neighborhoods random inside the urban center of the city through a field survey and the impact of that change on the morphological features of the city. The town of Mahmoudiya, one of the haunted Baghdad province to the south of the capital Baghdad, about 29 km towards the city of Hilla, an area within the municipal boundaries of more than 17 km 2 is equivalent to 1700 hectares, and accounted for 6.9% of the total elimination of space adult total 1452 km 2 which is equivalent to 145 200 hectares. The city experienced a population increase for large period between 2000-2014 amounted to more than 15,000 people, with an estimated population of the city - the center - for the year 2000 by about 78 625 people compared with the last census of the city was in 1997, as it appeared that the population of the city - the center arrived 64 817 people, an annual growth rate of the population was estimated at 3.2%, while the population reached according to the latest census of the city to more than 100,000 people as a result of increased population and natural in the number of births and low mortality rate and population migration from the surrounding countryside or nearby cities. The number of slums in the city center and its outskirts eight slums map within the residential use of the center town of Mahmudiyah, has been the study of three residential neighborhoods and is a model Random Alnor- neighborhood Almertdy- neighborhoods Abu wax .